2021
DOI: 10.2991/assehr.k.211219.035
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Eighth Grader’s Mathematical Literacy Ability in Solving HOTS Questions at SMPN 3 Tarakan

Abstract: This research is a qualitative descriptive study that aims to describe students' mathematical literacy skills of class VIII SMPN 3 Tarakan in solving HOTS questions. The subject in this study was a class VII student. This study used a test instrument which was the HOTS problem, semi-structured interview guidelines, and student's score report cards. The research took two months. Based on the results of the study, the mathematical literacy abilities of grade VIII students in solving hots questions are at level 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Furthermore, students in the moderate mathematical ability group (S2) are at level 3 of mathematical literacy ability. Meanwhile, students in the high mathematical ability group (S3) are at level 4 of mathematical literacy ability, which means that they are still at the intermediate level; 3) Research conducted on 8th grade students at one of the Integrated Islamic Junior High Schools in Yogyakarta (Nurutami et al, 2018) showed the results that students with high math skills could achieve PISA math literacy level 2 and level 4, students with average math skills could achieve PISA math literacy level 2 , and students with low math skills cannot achieve mathematical literacy level 2, 3 or level 4 PISA; 4) Research conducted on 8th grade students at SMP N 3 Tarakan, North Kalimantan (Rahayu, 2022) showed that the mathematical literacy skills of class VIII students in solving hots questions were at level 4, namely: effectively work with models in concrete but complex situations limited in making assumptions, selecting and combining different representations, relating to real situations, using limited skills with few clear contextual views; 5) Research conducted on 8th grade students at Sultan Agung 4 Islamic Junior High School Semarang, Central Java (Ovan et al, 2018) showed that students with low metacognition had poor mathematical literacy skills, students with moderate metacognition had quite good mathematical literacy skills, and students with high metacognition had literacy skills math is very good; 6) Research on 8th graders at SMP Negeri 1 Tulis (Dessy Eka Jayanti, St. Budi Waluya, 2014) showed that the maximum students' mathematical literacy ability was at level 4, the mathematical literacy test was focused on real-life problems, outside of situations or problems that are often discussed in class during the mathematics learning process; 7) The research was conducted on 9th grade students at SMP Islam Al Azhar 27 Cilegon (Muslimah & Pujiastuti, 2020), which showed that students in the low mathematical ability group (S1) were at level 2 of mathematical literacy ability. Furthermore, students in the moderate mathematical ability group (S2) are at level 3 of mathematical literacy ability.…”
Section: Number Of Studimentioning
confidence: 99%
“…Furthermore, students in the moderate mathematical ability group (S2) are at level 3 of mathematical literacy ability. Meanwhile, students in the high mathematical ability group (S3) are at level 4 of mathematical literacy ability, which means that they are still at the intermediate level; 3) Research conducted on 8th grade students at one of the Integrated Islamic Junior High Schools in Yogyakarta (Nurutami et al, 2018) showed the results that students with high math skills could achieve PISA math literacy level 2 and level 4, students with average math skills could achieve PISA math literacy level 2 , and students with low math skills cannot achieve mathematical literacy level 2, 3 or level 4 PISA; 4) Research conducted on 8th grade students at SMP N 3 Tarakan, North Kalimantan (Rahayu, 2022) showed that the mathematical literacy skills of class VIII students in solving hots questions were at level 4, namely: effectively work with models in concrete but complex situations limited in making assumptions, selecting and combining different representations, relating to real situations, using limited skills with few clear contextual views; 5) Research conducted on 8th grade students at Sultan Agung 4 Islamic Junior High School Semarang, Central Java (Ovan et al, 2018) showed that students with low metacognition had poor mathematical literacy skills, students with moderate metacognition had quite good mathematical literacy skills, and students with high metacognition had literacy skills math is very good; 6) Research on 8th graders at SMP Negeri 1 Tulis (Dessy Eka Jayanti, St. Budi Waluya, 2014) showed that the maximum students' mathematical literacy ability was at level 4, the mathematical literacy test was focused on real-life problems, outside of situations or problems that are often discussed in class during the mathematics learning process; 7) The research was conducted on 9th grade students at SMP Islam Al Azhar 27 Cilegon (Muslimah & Pujiastuti, 2020), which showed that students in the low mathematical ability group (S1) were at level 2 of mathematical literacy ability. Furthermore, students in the moderate mathematical ability group (S2) are at level 3 of mathematical literacy ability.…”
Section: Number Of Studimentioning
confidence: 99%